The epistles of Paul to the Philippians the English text with introduction, exposition and notes - Muller, Jacobus J., d.1977 (Grand Rapids, MI Eerdmans, 1955)
Includes bibliographical references and indexes.
First published in June 1955 as part of The epistles of Paul to the Philippians and to Philemon. Reprinted 1988.
Keywords: Bible. N.T. Philippians -- commentaries